2015
DOI: 10.1097/wnf.0000000000000093
|View full text |Cite
|
Sign up to set email alerts
|

Five Patients With Burning Mouth Syndrome in Whom an Antidepressant (Serotonin-Noradrenaline Reuptake Inhibitor) Was Not Effective, but Pregabalin Markedly Relieved Pain

Abstract: Burning mouth syndrome (BMS) causes idiopathic pain or a burning sensation in clinically normal oral mucosa. Burning mouth syndrome is a chronic disease with an unknown etiology. Burning mouth syndrome is also idiopathic, and a consensus regarding diagnosis/treatment has not been reached yet. Recent studies have supported the suggestion that BMS is a neuropathic pain disorder in which both the peripheral and central nervous systems are involved. Tricyclic antidepressants (nortriptyline and amitriptyline), sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Recently, it was hypothesized that these conditions may actually represent neuropathic pain. Although they may be caused by peripheral sensitization, central sensitization, or impaired upper central nervous control function [1], pathophysiological diversity was observed, as we previously reported [2].…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…Recently, it was hypothesized that these conditions may actually represent neuropathic pain. Although they may be caused by peripheral sensitization, central sensitization, or impaired upper central nervous control function [1], pathophysiological diversity was observed, as we previously reported [2].…”
Section: Introductionmentioning
confidence: 64%
“…AS, HK, TT 2) , WN, MI and TM wrote this manuscript under supervision of KK, YN, NO 2) , EU, TT 6) and MO. AS, HK, TT 2) , TM, EU, MI and NO 5) designed the study. AS, WN, YK, SK and NO 5) performed the investigation and analyzed the data.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of many pharmacological agents, including pregabalin, 18) topiramate, 19) duloxetine, 20) pramipexol, 21) and olanzapine, 22,23) has been reported in isolated cases or case series. In the present study, we reported the effectiveness of new pharmacologic agents that had not been discussed previously in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Although the beneficial effects of duloxetine on refractory BMS have been documented in two studies [20,21], both studies are single case reports. In addition, another study reported contradictory results that the oral symptoms of one patient who was prescribed duloxetine did not improve [22]. Therefore, knowledge about the efficacy of venlafaxine and duloxetine on BMS is still insufficient.…”
Section: Introductionmentioning
confidence: 99%